PROBLEMATIKA PENGALIHAN PIUTANG BANK SECARA CESSIE TERHADAP DEBITUR (STUDI KASUS PUTUSAN NOMOR 142/PDT.G/2022/PN MDN) - Gladys Fiona Tantiani; Roswita Sitompul; O.K. Isnainul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Cessie is the transfer of receivables collection rights in the name and other intangible objects carried out by authentic deed or deed under hand. In Cessie the right to collect receivables is transferred to new creditors but District Court's ruling in case No. 142/PDT.G/2022/PNMDN gives the plaintiff the right to sell the collateral. Legal research is normative legal research. The data used are primary and secondary data obtained through interviews and literature studies. The data is analyzed qualitatively. The problems are the legal consequences of transferring Bank receivables cessie to new creditors, the judge's considerations in Decision Number 142/Pdt.G/2022/PNMdn, and legal protection of debtors and the implementation of the Decision Number 142/Pdt.G/2022/PNMdn. The consequence of transferring bank receivables by cessie is not only the right to collect receivables is transferred but the rights of creditors as holders of collateralized rights also transfer to new creditors. The execution of the debtor’s guarantee must be in accordance with applicable regulations, the creditor can’t necessarily own the collateral. It needs clearer regulation regarding the consequences of transferring bank receivables cessie in particular against the guarantee of liability. So, the regulation can provide legal protection and certainty for both cessus, cedent, and cessionaris.